2008
DOI: 10.1111/j.1467-937x.2008.00495.x
|View full text |Cite
|
Sign up to set email alerts
|

A Spatial Theory of News Consumption and Electoral Competition

Abstract: We characterize the optimal editorial positions of the media in a model in which the media influence both voting behaviour and party policies. Political parties are less likely to choose partisan policies when more voters consume informative news. When there are two media outlets, each should be slightly biased relative to its audience in order to attract voters with relatively extreme views. Voter welfare is typically higher under a duopoly than under a monopoly. Two media outlets under joint ownership may pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
99
2

Year Published

2008
2008
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 115 publications
(102 citation statements)
references
References 21 publications
1
99
2
Order By: Relevance
“…Similarly to other models of demand-driven media bias (e.g., Mullainathan and Shleifer, 2005;Annand et al, 2007;Chan and Suen, 2008), the results show that the higher the degree of competition in the market for news, the more likely that media outlets will choose ideological editors. That is, when the market for news gets crowded, a media outlet may prefer to differentiate its news product by choosing a different location in the policy space (i.e., choose an editor with different idiosyncratic characteristics), rather than sharing the demand for news of moderate citizens with the other media outlets.…”
Section: Discussionmentioning
confidence: 51%
See 2 more Smart Citations
“…Similarly to other models of demand-driven media bias (e.g., Mullainathan and Shleifer, 2005;Annand et al, 2007;Chan and Suen, 2008), the results show that the higher the degree of competition in the market for news, the more likely that media outlets will choose ideological editors. That is, when the market for news gets crowded, a media outlet may prefer to differentiate its news product by choosing a different location in the policy space (i.e., choose an editor with different idiosyncratic characteristics), rather than sharing the demand for news of moderate citizens with the other media outlets.…”
Section: Discussionmentioning
confidence: 51%
“…This result is typical in models of demand-driven media bias (e.g., Mullainathan and Shleifer, 2005;Annand et al, 2007;Chan and Suen, 2008). It follows from the incentives of profit-maximizing media outlets to differentiate their news products.…”
Section: Introductionmentioning
confidence: 84%
See 1 more Smart Citation
“…Papers that jointly determine campaign strategies, media behavior and voters' choices include Grossman and Helpman (1999);Strömberg (2004);Andina-Díaz (2004);Chan and Suen (2008);Carrillo and Castanheira (2008); Gul and Pesendorfer (2011);and Chakraborty, Ghosh, and Roy (2015). In Strömberg (2004), parties choose platforms that appeal to the median consumer of the media, rather than that of the voting population.…”
Section: Related Literaturementioning
confidence: 99%
“…Specifically, it has shown that there may be a "supply-driven" political media bias deriving from the idiosyncratic preferences of journalists (Baron, 2006), owners (Djankov et al, 2003; McLaren, 2010), governments (Besley and Prat, 2006) or lobbies (Sobbrio, 2010;Petrova, 2011). Moreover, the endogenous demand of politically "slanted" news by viewers may result in a "demand-driven" bias in news reports (Mullainathan and Shleifer, 2005;Gentzkow and Shapiro, 2006;Chan and Suen, 2008;. While the literature has been trying to address the sources and the welfare implications of political media bias, less attention has been devoted to analyze the advertisers-induced distortions in the informative contents of media outlets, i.e., to commercial media bias (Ellman and Germano, 2009;Germano and Meier, 2010).…”
mentioning
confidence: 99%